STABILITAS SERBUK PEWARNA ALAMI BERBASIS ANTOSIANIN BUAH NAGA MERAH APKIR TERVARIASI PELARUT ASAM DALAM BERBAGAI KONDISI EKSTERNA - Oryzatania Windaru Runteka; Miftahul Choiron; Eka Ruriani; Maria Belgis; Andi Eko Wiyono (Jurnal Agritechno, 2022)
Anthocyanins are red, purple, blue pigments in low quality red dragon fruit which have potential as a source of natural dyes. Anthocyanins are more stable when an acid solvent is added because it can strengthen the anthocyanin color during the drying process. This study aims to determine the stability of the natural dye powder of an off grade red dragon fruit with the addition of a acid solvent under various pH conditions, high temperature heating time, storage temperature conditions, adding salt and adding sugar, as well as knowing the best treatment for the stability test of natural dyes powder with the addition of a acid solvent. In this study the stability test of the natural dyes powder was tested with variations in the types of acid solvent namely citric acid and ascorbic acid in concentrations of 0.3% and 3%. The data on the stability test results of the dye powder are presented in the form of tables and graphs and described descriptively. Determination of the best treatment was analyzed by the spider web method The results of the stability test of natural dye powder showed that treatment A1 with the addition of 0.3% citric acid was the best treatment because A1 dye powder was able to be more stable stored in a refrigerator temperature of 10⁰C for 7 days, stable in variations of citric acid buffer solution pH 3-6, stable in heating for 0-45 minutes, and also stable in 2%, 4%, and 6% salt solutions. The dye powder which is able to be stable at room temperature storage conditions of 27⁰C is A4 dye powder, and the dye powder which is stable in various sugar concentrations of 20%, 40%, and 60% is A2 dye powder.